PENERAPAN MODEL PEMBELAJARAN PQ4R (PREVIEW, QUESTION, READ, REFLECT, RECITE, REVIEW) UNTUK MENINGKATKAN HASIL BELAJAR PKN SISWA KELAS IV SDN 25 DESA PAKNING ASAL KECAMATAN BUKIT BATU KABUPATEN BENGKALIS - Dessy Afriani; Zariul Antosa; Lazim N Lazim N (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract :This study in the background backs by low learning outcomes PKn students, with an average grade 62.78. Among students who were 18 people only 5 students who completed KKM with classical completeness reach 27.78%. PQ4R learning model is the learning that is used to help students remember what they learn and can help the learning process in classes conducted by the activities reading books. PQ4R a model of excellence is to help students whose power is weak memory to memorize the concepts of learning, helping students to improve their skills and processes asked to consume knowledge. This research is a classroom action research (PTK) conducted aims to improve learning outcomes PKn fourth grade students of SDN 25 Desa Pakning-Bukit Batu subdistrict Origin by applying the learning model PQ4R (Preview, Question, read, reflect, Recite, review). Data collection instruments in this thesis is the teacher and student activity sheets and the results of this belajar.Skripsi serving an increasing number of students who reach the KKM of 5 people (27.78%) on the base score to 12 people (66.67%) in the first cycle and increased to 16 people (88.89%) in the second cycle. This means that the sample classes have been completed in the classical. At the first meeting of the first cycle of teacher activity percentage was 50% 66.67% .Sedangkan second meeting of the second cycle of the first meeting with the percentage of 79.17% and the second meeting increased to 91.67%. While the student activity also increased that the first meeting of the first cycle of the percentage of student activity is 50%, 61.12% second meeting, the first meeting of the second cycle of 72.23% and 83.34% second meeting. Improving student learning outcomes individually from a base score until the second cycle increased, where the average base score of student learning outcomes 62.78 in the first cycle increased to 64.73 with an increase of 1.95. In the second cycle of the average student learning outcomes for 78,34dengan increase of 13.61. Improving student learning outcomes in the classical style on the base score is 27.78% in the first cycle increased to 66.67 increased 38.89% and in the second cycle increased to 88.89 an increase of 22.22%. After analyzing the research data, the application of the model PQ4R can improve learning outcomes PKn class IV SDN 25 Pakning Origin village.Keywords : PQ4R (Preview, Question, Read, Reflect, Recite, Review), the result of studying Civics